2005
DOI: 10.1021/jp0511606
|View full text |Cite
|
Sign up to set email alerts
|

Sticking Probability on Zeolites

Abstract: The sticking coefficient, i.e., the probability that, on hitting the surface of a nanoporous particle (zeolite), a molecule shall be able to enter the intracrystalline space, is a key quantity for the application of such materials in heterogeneous catalysis and molecular sieving. On the basis of pulsed field gradient NMR diffusion measurements and molecular dynamics simulations, typical values of this probability are found to be close to one. They exceed previous estimates on the basis of IR uptake measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
3
25
2
Order By: Relevance
“…The steps of sticking and trapping of the sorbate on the zeolite surface and of entering into the pore network are probably most controversially discussed. Simon et al reported estimated sticking probabilities of approximately one [74,75] for n-butane on silicalite-1 and Kärger et al [76] of around 10 −4 for benzene in silicalite-1 using PFG-NMR [76,77]. In contrast, our results on the basis of time-resolved infrared spectroscopy with ZSM5 [78] showed values of around 10 −7 for benzene, toluene, and xylene.…”
Section: Introductioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The steps of sticking and trapping of the sorbate on the zeolite surface and of entering into the pore network are probably most controversially discussed. Simon et al reported estimated sticking probabilities of approximately one [74,75] for n-butane on silicalite-1 and Kärger et al [76] of around 10 −4 for benzene in silicalite-1 using PFG-NMR [76,77]. In contrast, our results on the basis of time-resolved infrared spectroscopy with ZSM5 [78] showed values of around 10 −7 for benzene, toluene, and xylene.…”
Section: Introductioncontrasting
confidence: 75%
“…The process of entering the zeolite pores involves external or internal diffusion barriers [30,79,80], the size exclusion during the pore entry [74,81], and the subtle interplay between entropic and enthalpic effects during sorption within confined spaces [54]. The differentiation between these effects, presumably occurring simultaneously, is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The sticking coefficient can vary by orders of magnitude. It can be very close to 1, as observed for n-butane in silicalite- [67], or be several orders lower, as found by Jentys et al [68] for benzene, toluene, and xylene on ZSM-5. Clear guidelines for which systems low sticking coefficients can be expected are still lacking.…”
Section: Surface Barrierssupporting
confidence: 61%
“…Such probabilities have been estimated on the basis of both PFG NMR [78,79] and IR [80 -83] experiments, as well as by MD simulations [78]. Depending on the system under study, probabilities from as small as 10 -7 [80 -82] to close to one [78,79] have been obtained. Monitoring the evolution of guest profiles in nanoporous materials provides a new and direct access to the sticking probabilities of nanoporous particles.…”
Section: "Sticking" Probabilitiesmentioning
confidence: 99%